2013
DOI: 10.1289/ehp.1206145
|View full text |Cite
|
Sign up to set email alerts
|

Improved Air Quality and Attenuated Lung Function Decline: Modification by Obesity in the SAPALDIA Cohort

Abstract: Background: Air pollution and obesity are hypothesized to contribute to accelerated decline in lung function with age through their inflammatory properties.Objective: We investigated whether the previously reported association between improved air quality and lung health in the population-based SAPALDIA cohort is modified by obesity.Methods: We used adjusted mixed-model analyses to estimate the association of average body mass index (BMI) and changes in particulate matter with aerodynamic diameter ≤ 10 µm (PM1… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
37
3
1

Year Published

2013
2013
2022
2022

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 55 publications
(42 citation statements)
references
References 51 publications
1
37
3
1
Order By: Relevance
“…We found no study with stratified analysis on BMI or dietary factors, despite of the known association between BMI and asthma [43]. Several papers suggested that obesity can play a role in susceptibility to pollutants effects [41,42] in lung function, and in a randomized-trial [56] antioxidant intake was associated with a moderate impact of ozone exposure on lung function in children with moderate to severe asthma. Whereas susceptibility of older adults to the health effects of air pollution is well recognized, and particularly on lung function [57] where frailty was associated with a higher decline of forced vital capacity due to air pollution, we did not find study stratifying on these factors.…”
Section: Overall Discussion and Conclusionmentioning
confidence: 77%
See 1 more Smart Citation
“…We found no study with stratified analysis on BMI or dietary factors, despite of the known association between BMI and asthma [43]. Several papers suggested that obesity can play a role in susceptibility to pollutants effects [41,42] in lung function, and in a randomized-trial [56] antioxidant intake was associated with a moderate impact of ozone exposure on lung function in children with moderate to severe asthma. Whereas susceptibility of older adults to the health effects of air pollution is well recognized, and particularly on lung function [57] where frailty was associated with a higher decline of forced vital capacity due to air pollution, we did not find study stratifying on these factors.…”
Section: Overall Discussion and Conclusionmentioning
confidence: 77%
“…-Body mass index (BMI): subjects with obesity have been found to be more susceptible to air pollution in terms of lung function (and as lung function is an asthma related phenotype, it seems plausible that susceptibility factors related to lung function may also be interesting to study regarding asthma incidence) and asthma [41][42][43].…”
Section: Susceptibility Factorsmentioning
confidence: 99%
“…For example, improvements were not observed in symptoms following an allergen-reducing indoor air quality intervention in a public housing complex among asthmatic children reporting exposure to a psychosocial risk factor (e.g., fear of violence) [55]. Similarly, improved air quality was associated with a slower rate of decline in several lung function parameters among non-obese but not among obese participants in a study of Swiss adults [56]. Counter to initial hypotheses, those with factors typically thought to confer increased susceptibility to the adverse effects of air pollution exposures (e.g., psychosocial factors and obesity) did not experience greater benefits following reductions in air pollution exposures.…”
Section: Who Benefits From Cleaner-burning Cookstove Interventions Anmentioning
confidence: 99%
“…Although previous reports have shown significant synergistic effects of obesity and exposure to ambient air pollutants such as nitrogen dioxide (NO 2 ) and PM 10 content on lung function using an indirect measurement of obesity including body mass index (BMI), 6,13,14 accurate quantitative measurement of adipose tissue mass by computed tomography (CT) is needed to understand the plausible mechanisms between adipose tissue and air pollution in lung function. However, to our knowledge, no studies have investigated whether there is an additive effect of fat accumulation in adipose tissue on the relationship between ambient air pollution and lung function.…”
Section: Introductionmentioning
confidence: 99%